Mentalization based treatment of youth on the psychotic spectrum: clinical profiles and outcomes for youth in the ECID - Dangerfield, Mark; Brotnow Decker, Line (Frontiers in Psychiatry, 2023)
Introduction Early intervention may significantly improve the prognosis associated with psychotic disorders in adulthood. Methods The present study examined the acceptability and effectiveness of a standalone intensive, in-home, mentalization-based treatment (MBT) for extremely high-risk, non-help-seeking youth on the psychotic spectrum [Equipo Clínico de Intervención a Domicilio (ECID), Home Intervention Clinical Team]. Results Despite previously being unable to participate in treatment, more than 90% of youth engaged and those on the psychotic spectrum demonstrated slightly higher engagement than the general high-risk group (95% and 85%, respectively, X1 = 4.218, p = 0.049). Generalized estimating equation (GEE) models revealed no main group effect on the likelihood of reengaging with school over the first 12 months of treatment (X1 = 1.015, p = 0.314) when controlling for the duration of school absenteeism at intake. Overall, the percentage of school engagement rose from 12 to 55 over this period, more than 40% of the total sample experienced clinically reliable change and an additional 50% appeared clinically stable. No statistically significant difference was observed between the groups in the average change in HoNOSCA total severity score (X1 = 0.249, p = 0.618) or the distribution of youth into categories of clinical change during the first year of treatment (X1 = 0.068, p = 0.795). Discussion The present findings suggest that a mentalization based intervention may be able to engage extremely high-risk youth in treatment and have clinically meaningful impact on symptom severity and functioning after 12 months.